A measured pace : toward a philosophical understanding of the arts of dance - Sparshott, Francis Edward, 1926-2015 (Toronto studies in philosophy., 1995)
Although the theoretical importance of dance has always been recognized, dance has been relatively neglected in the philosophy of art. In this sequel to Off the Ground, in which Professor Sparshott focused on the concept of dance in general, A Measured Pace considers the recognized classification of dance as art, its values, and relationship to the other arts. Sparshott begins with an explanation of the philosophical importance of the major classifications of dance and their basis. He examines dance as a mimetic and expressive medium, and reviews the major dimensions of dance form. He then explores the relationship of dance to three related fields: music, language, and theatre. Sparshott also discusses the major philosophical problems of dance as an art: the specific values of dance; the relation between the way the audience perceives dance and the dancer's self-perception; the ways in which dancing and dances are learned; the division of artistic creation between choreographers and performers; and the ways in which dances are identified and retain their identity through time. A concluding chapter on how dances are recorded considers how the media may change the nature of dance. A Measured Pace is a wide-ranging and substantial contribution to a philosophical understanding of dance.